2011
DOI: 10.1371/journal.pone.0020313
|View full text |Cite
|
Sign up to set email alerts
|

Visual Information Alone Changes Behavior and Physiology during Social Interactions in a Cichlid Fish (Astatotilapia burtoni)

Abstract: Social behavior can influence physiological systems dramatically yet the sensory cues responsible are not well understood. Behavior of male African cichlid fish, Astatotilapia burtoni, in their natural habitat suggests that visual cues from conspecifics contribute significantly to regulation of social behavior. Using a novel paradigm, we asked whether visual cues alone from a larger conspecific male could influence behavior, reproductive physiology and the physiological stress response of a smaller male. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 69 publications
1
55
0
Order By: Relevance
“…To make this decision, a fish needs as much information about the opponent as possible. Although the roles of visual and chemosensory signals in animal assessment are well documented (Arnott and Elwood, 2009;Bleckmann and Mogdans, 2014;Chen and Fernald, 2011;Ratterman et al, 2009), only one study has examined the role of the lateral line system in mediating mutual assessment (Butler and Maruska, 2015). In that study, we found that lateral-line-ablated male cichlids were less likely to initiate and engage in a territorial encounter compared with lateral-line-intact males ( Fig.…”
Section: Mechanosensory Signals and Aggressive Interactionsmentioning
confidence: 82%
See 1 more Smart Citation
“…To make this decision, a fish needs as much information about the opponent as possible. Although the roles of visual and chemosensory signals in animal assessment are well documented (Arnott and Elwood, 2009;Bleckmann and Mogdans, 2014;Chen and Fernald, 2011;Ratterman et al, 2009), only one study has examined the role of the lateral line system in mediating mutual assessment (Butler and Maruska, 2015). In that study, we found that lateral-line-ablated male cichlids were less likely to initiate and engage in a territorial encounter compared with lateral-line-intact males ( Fig.…”
Section: Mechanosensory Signals and Aggressive Interactionsmentioning
confidence: 82%
“…In teleost fishes, the use of visual, chemosensory and acoustic communication is relatively well studied in different behavioral contexts such as territoriality, reproduction and parental care (Almeida et al, 2005;Amorim et al, 2003Amorim et al, , 2004Barata et al, 2007;Chen and Fernald, 2011;Grosenick et al, 2007;Keller-Costa et al, 2015;Korzan and Fernald, 2007;Korzan et al, 2008;Lobel, 1998;MartinovicWeigelt et al, 2012;Rosenthal and Ryan, 2000;Simoes et al, 2008). However, all fishes also possess another sensory system, the mechanosensory lateral line (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of the smaller male was typical of an animal losing his territorial status, leaving the shelter and excavating a new pit at the opposite corner of the tank. The changes in the smaller male resulted entirely from visual information, which also produced a reduction in androgen hormone expression for the first 3 days after removal of the black barrier (Chen and Fernald, 2011). Seven days after the visual exposure began, the smaller male had normal hormone levels but retained the coloration of a ND male.…”
Section: Male Deceptionmentioning
confidence: 99%
“…Clearly, this kind of ability, when used to gain advantage over competitors, could potentially be very useful. To determine whether A. burtoni males deceive each other with regard to their social status, Chen and Fernald (2011) placed a large male and a small male fish with an appropriately sized female in an aquarium with a 'shared' terracotta pot shelter, divided into halves by a removable opaque and watertight transparent partition (Fig. 5).…”
Section: Male Deceptionmentioning
confidence: 99%
See 1 more Smart Citation